(untitled) (Marketing Journal, 2025)
This article describes the issues of improving the accounting and internal control of biological assets in fisheries based on international standards. That is, analytical accounts to take into account the biotransformation of fish and recommendations for the accounting of economic operations related to the biotransformation of biological 30 assets in fisheries, as well as the issues of inventorying the process from larvae to commercial fish in fisheries are covered. Conclusions and proposals were formed.